(untitled) (Journal of Education and Development, 2020)
Gamification is only successful if the key elements are joint and run in unity in favour of the user, and knowing game-playing characteristics of target audience is of utmost importance. This study aimed to identify the students’ game-playing preferences and styles, considering the opportunity to implement gamification in education in a personalized way. A descriptive-normative survey involved 74 students of a Vocational Education and Training (VET) Institution, chosen by convenience sampling. The target audience of the research was students at the MQF introductory level A and B (17.6%), at MQF level 2 (40.5%) and at MQF level 3 (41.91%). Participants received a questionnaire about game-playing preferences and styles. Students’ average age was